Morphological Characterization and Transcriptional Regulation of Corolla Closure in Ipomoea purpurea - Zhang, Peipei; Sun, Mingyue; Wang, Xiaoqiong; Guo, Runjiu; Sun, Yuchu; Gui, Mengyuan; Li, Jingyuan; Wang, Taixia; Zhang, Liang (Frontiers in Plant Science, 2021)
Corolla closure protects pollen from high-temperature stress during pollen germination and fertilization in the ornamental plant morning glory (Ipomoea purpurea). However, the morphological nature of this process and the molecular events underpinning it remain largely unclear. Here, we examined the cellular and gene expression changes that occur during corolla closure in the I. purpurea. We divided the corolla closure process into eight stages (S0-S7) based on corolla morphology. During flower opening, bulliform cells appear papillate, with pigments in the adaxial epidermis of the corolla. These cells have distinct morphology from the smaller, flat cells in the abaxial epidermis in the corolla limb and intermediate of the corolla. During corolla closure, the bulliform cells of the adaxial epidermis severely collapse compared to cells on the abaxial side. Analysis of transparent tissue and cross sections revealed that acuminate veins in the corolla are composed of spiral vessels that begin to curve during corolla closure. When the acuminate veins were compromised, the corolla failed to close normally. We performed transcriptome analysis to obtain a time-course profile of gene expression during the process from the open corolla stage (S0) to semi-closure (S3). Genes that were upregulated from S0 to S1 were enriched in the polysaccharide degradation pathway, which positively regulates cell wall reorganization. Senescence-related transcription factor genes were expressed beginning at S1, leading to the activation of downstream autophagy-related genes at S2. Genes associated with peroxisomes and ubiquitin-mediated proteolysis were upregulated at S3 to enhance reactive oxygen species scavenging and protein degradation. Therefore, bulliform cells and acuminate veins play essential roles in corolla closure. Our findings provide a global understanding of the gene regulatory processes that occur during corolla closure in I. purpurea.